Immediate Implant Placement in Non-Infected Sockets versus Infected Sockets: a Systematic Review and Meta-Analysis - Aza Saijeva; Gintaras Juodzbalys (eJournal of Oral Maxillofacial Research, 2020)
Objectives: The aim of this systematic review is to compare immediate implant placement in infected extraction sockets with non-infected extraction sockets in terms of implant survival and function.